Problematika Perjalanan Dakwah Rasulullah Saw. Hingga Menemukan Jalan Keluar Dalam Buku “Muhammad Sang Yatim” Menurut Prof. Dr. Muhammad Sameh Said - Tias, Nadila Aprilia Ning (Maliki Interdisciplinary Journal, 2024)
Muslims are now facing a very difficult situation. Those who are Muslims prefer to fight each other rather than unite in the frame of afama, thought, and fate. even like to disbelieve each other, fight for worldly interests, and shed blood in the name of religion. At the same time, the enemies of Islam freely and fearlessly insult Allah and His Messenger through various media, violate the honor of their followers, damage the purity of Islamic symbols, and insult the elderly, women, and children. Look at what is happening in Muslim countries today in the world. In addition, the enemy has terrible war equipment and media, which are the result of advances in technology and science. The book Muhammad the Orphan, “The Promise and the Triumph to Look Forward to”, seeks to present the figure of the Prophet Muhammad from his humanist point of view, so that he could convey great compassion to everyone, even his enemies. We want to approach the image of the Great Hero who has changed human history to the young generation of Islam through the language used in literature and a perspective that suits the way of thinking of this century. A perfect picture of our Prophet’s childhood, when he was a child, even an orphan, then a teenager, married, became a father, and finally a grandfather. Finally, it was this Orphan who made human history more civilized and humane.